2014
DOI: 10.1007/s11218-014-9274-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in students’ school motivation: A latent class modelling approach

Abstract: In this study, we investigated the school motivation of 7,257 9th grade students in 80 secondary schools across the Netherlands. Using a multiple goal perspective, four motivation dimensions were included: performance, mastery, extrinsic, and social motivation. Our first aim was to identify distinct motivation profiles within our sample, using the four motivation dimensions in a latent class analysis. Our second aim was to investigate the relationships between students' school motivation profiles and several e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
50
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 69 publications
(134 reference statements)
12
50
3
2
Order By: Relevance
“…This is in line with observations from previous studies which generally showed that males were more likely to pursue performance goals (Anderman & Young, 1994;Linnenbrink et al, 1999) or to be more frequently represented in performance-driven profiles (Levy-Tossman et al, 2007). Korpershoek et al (2015) and Shim and Finch (2014) identified profiles characterized by low levels on all goals, corresponding to the Moderately Unmotivated profile identified here among 17% of the females. The absence of a similar profile among males might be related to the greater representation of males (41%) in the Social Power and Rewards Oriented profile, which presents relatively low levels on most goals, save for social power and rewards.…”
Section: Gender Differentiation and Similarity In Achievement Goal Prsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with observations from previous studies which generally showed that males were more likely to pursue performance goals (Anderman & Young, 1994;Linnenbrink et al, 1999) or to be more frequently represented in performance-driven profiles (Levy-Tossman et al, 2007). Korpershoek et al (2015) and Shim and Finch (2014) identified profiles characterized by low levels on all goals, corresponding to the Moderately Unmotivated profile identified here among 17% of the females. The absence of a similar profile among males might be related to the greater representation of males (41%) in the Social Power and Rewards Oriented profile, which presents relatively low levels on most goals, save for social power and rewards.…”
Section: Gender Differentiation and Similarity In Achievement Goal Prsupporting
confidence: 92%
“…In line with prior research showing the benefits of adopting mastery or social goals alone King et al, 2010Watkins, McInerney, & Lee, 2002) or in combination (Korpershoek et al, 2015;Shim & Finch, 2014;Wentzel, 1993), the Mastery-Socially Oriented profile was associated with desirable outcomes for males and females. Perhaps more interesting is the observation that the Social Power and Praise Oriented profile presented similar outcomes levels as the Mastery-Socially Oriented profile.…”
Section: Outcomes Of Achievement Goal Profilessupporting
confidence: 87%
See 2 more Smart Citations
“…In a previous publication using the same dataset, latent cluster analysis was used to define student groups with different motivational profiles (Korpershoek, Kuyper, & Van der Werf, 2015). It was found that the student group with high scores on all motivation dimensions (i.e.…”
Section: Relationships Between the Two Constructsmentioning
confidence: 99%